Emergency Nursing Care of Ineffective Breathing Patterns in Epilepsy Patients : Case Study - Faidana Yaumil Syifa; Nur Hijrah Tiala (Sean Institute, 2024)
Epilepsy is a non-communicable disease that attacks the brain due to excessive electrical discharge characterized by seizures of all or part of the body accompanied by loss of consciousness. In Indonesia, epilepsy is commonly called ayan or sawan. The number of epilepsy sufferers worldwide is around 50 million and the number in Indonesia is around 1.5-2.4 million. The highest incidence of epilepsy is in those over 50 years of age, which is 28.4 per 100,000 people. The highest mortality rate is in the elderly. The purpose of this study was to determine emergency nursing care for Mr. A with a medical diagnosis of epilepsy in the emergency room. The method used is the case study method by carrying out nursing care including assessment, diagnosis, intervention, implementation and evaluation. The study was conducted in the emergency room of Urip Sumoharjo Hospital on Mr. A on June 10, 2024. The results of the study found a nursing diagnosis of ineffective breathing patterns related to neurological disorders (seizure disorders) characterized by dyspnea. Interventions carried out for 1x24 hours, the expectation of breathing patterns improved with the criteria for decreasing dyspnea results. Conclusion, responsive nursing care for epilepsy patients in the emergency room can prevent recurrent seizures, reduce morbidity and mortality due to epilepsy.